(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze innovations in social studies learning media through the integration of weblogs as digital portfolios in the era of digital literacy. The phenomenon examined relates to the limited utilization of digital media that supports reflective and participatory learning. This study employs a qualitative approach using a library research method through a systematic analysis of relevant scientific literature. The data sources consist of indexed scientific articles obtained from Google Scholar, Scopus, and SINTA-indexed journals published between 2020 and 2025. Data collection was conducted through a systematic literature search involving identification, selection, and document review stages. Data analysis utilized thematic analysis combined with the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings identify four main themes: weblogs as digital literacy-based learning media, their function as reflective digital portfolios, increased student engagement, and implementation challenges. The results indicate that weblogs are capable of integrating learning and assessment processes holistically while supporting constructive and reflective learning. Theoretically, this study contributes to the development of digital learning media literature, while practically it provides guidance for educator